Preserving Indonesian heritage: a linguistic and cultural study of traditional sports terminology in Bahasa Indonesia - Erinda Dwimagistri Sukmana; Daroe Iswatiningsih; Akhmad Munib; Ilham Mustofa; Arifana Arifana; Firdaus Firdaus; Gemala Widiyarti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: The indigenous games of Indonesia have been culturally significant in local customs, rituals, and social life. At this level of intangible cultural heritage, these sports are the preservers not just of physical entertainment, but language, identity, and regional knowledge passed from a people’s ancestors.